Development of science-techniology organizations in key economic areas in Vietnam - Hanh, Nguyen Thi Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Regional science-technology (S&T) organizations, in the world over, play key important roles in supporting socio-economic development of regions. They naturally make part of the system of S&T organization of the nation. In Vietnam the need of establishment of a system of S&T organizations in key economic areas was mentioned officially in some important administration documents in relation to S&T sectors, namely: Resolution No. 20-NQ/TW, 01November 2012 of the 6-th Conference, Party Central Committee, Session XI, on S&T development to serve industrialization and modernization in conditions of socialist oriented market economy and international integration; Strategies for S&T development, 2011-2020 period (issued together with Decision No. 418/QD-TTg, 11 April 2012 by the Prime Minister) and others. As contributions to implementation of the Party guiding lines in practice, the paper provides a focused analysis of some aspects: S&T organizations in regional innovation system; Status of development of regional S&T organizations in key economic areas in Vietnam and some recommendations for development of S&T organizations in key economic areas in future time.